CDKN2A/B Deletion and Double-hit Mutations of the MAPK Pathway Underlie the Aggressive Behavior of Langerhans Cell Tumors. (February 2018) - Xerri, Luc; Adélaïde, José; Popovici, Cornel; Garnier, Séverine; Guille, Arnaud; Mescam-Mancini, Lenaïg; Laurent, Camille; Brousset, Pierre; Coze, Carole; Michel, Gérard; Chaffanet, Max; Bouabdallah, Reda; et al.
Abstract : Langerhans cell histiocytosis (LCH) has a mostly favorable outcome, whereas Langerhans cell sarcoma (LCS) is an aggressive tumor. It is still unclear whether any specific molecular alterations could underlie the aggressive behavior of Langerhans cell proliferations. We used targeted next-generation sequencing and array-comparative genomic hybridization to profile 22 LCH samples from different patients together with 3 LCS samples corresponding to different relapses from the same patient. The third LCS relapse was a composite tumor including both B-cell chronic lymphocytic leukemia and LCS components. The 22 LCH samples were mostly of bone origin and showed classic histophenotypical features. Array-comparative genomic hybridization showed in all 3 LCS samples a similar homozygous somatic loss affecting the CDKN2A/B locus, whereas the 17 informative LCH samples did not show any detectable abnormality. In the 3 LCS samples, targeted next-generation sequencing of 495 cancer genes detected common mutations in KMT2D/MLL2 and in both MAP2K1 and NRAS genes, whereas BRAF was not mutated. A NOTCH1 mutation was acquired in 2 LCS samples. The composite LCS/B-cell chronic lymphocytic leukemia tumor showed the same genetic profile in its 2 components. LCH samples showed mutually exclusive mutations of BRAF (8/20) and MAP2K1 (4/19), but no mutation of KMT2D, NRAS nor NOTCH1 . These results suggest that CDKN2A/B deletion and/or simultaneous mutations of MAP2K1 and NRAS may underlie the aggressive behavior of Langerhans cell tumors, and thus could be useful for the diagnosis of malignancy in histiocytic neoplasms. The MAPK pathway "double hit" profile provides a basis for targeted therapy in LCS patients.